The Employment of ATR-FTIR Spectroscopy and Chemometrics for Authentication of Bawal (Colossoma macromopum) Fish Oil from Palm Oil - Anggriani, Firhani; Rohman, Abdul; Martien, Ronny (Journal of Food and Pharmaceutical Sciences, 2024)
Fish is a product with high nutritional content, and the development of fish oil has made it easier for consumers to consume. High-quality fish oil can be a target for adulteration, such as with vegetable oils like palm oil. FTIR spectroscopy was developed for the authentication of bawal fish oil (BFO) from palm oil (PO). Bawal fish oil and palm oil were prepared in binary mixtures with concentrations from 0-100%, resulting in 21 mixtures. The oil was directly measured by attenuated total reflectance (ATR) spectral measurement in the mid-infrared region (4000-600 cm-1). The results were combined with linear discriminant analysis (LDA) and multivariate calibration, such as PLSR or PCR. The results showed that LDA could make clear discrimination between bawal fish oil, palm oil, and their mixtures without any misclassification observed. Multivariate calibration with PLSR using the first derivative spectrum provided the best model for the relationship between actual and predicted FTIR values. At this conditions, the R2 values for the calibration and validation models obtained were 0.9966 and 0.9969, with RMSEC and RMSEP values of 0.0249 and 0.0248, respectively. Therefore, FTIR spectroscopy combined with LDA and PLSR is an effective method for authenticating bawal fish oil from palm oil.